Construction of cyclic DNA codes over the ring Z4[u]/〈u2−1〉 based on the deletion distance - Hai Q. Dinh (2018)
© 2018 Elsevier B.V. We develop the theory for constructing DNA cyclic codes of odd length over R=Z4[u]/〈u2−1〉 based on the deletion distance. Cyclic codes of odd length over R satisfying the reverse constraint and the reverse-complement constraint are discussed. The GC-content of these codes and their deletion distance are studied. Among others, examples of cyclic DNA codes with GC-content and their respective deletion distance are provided.